Effects of solid lubricants on the tribological behavior of steel‐backed UHMWPE fabric composites. Issue 8 (20th September 2021) - Lin, Yudong; Guo, Zhiwei; Yuan, Chengqing
Abstract: Aboard ship, the use of lubricating oil in mechanical equipment is sometimes difficult to achieve and applied oil can easily leak. The use of self‐lubricating materials can largely solve this problem. In this study, three kinds of solid lubricant‐enhanced 304 stainless steel‐backed ultrahigh molecular weight polyethylene (UHMWPE) fabric composites were fabricated with the addition of graphite, molybdenum (IV) disulfide, or polytetrafluoroethylene (PTFE). They were tested under various rotating speeds and compared with pure steel‐backed UHMWPE fabric composites. The tribological performance of these composites was evaluated by analysis of friction coefficient, wear rate, and worn face morphology. The results showed that PTFE‐enhanced composites exhibited the best friction reduction performance under all test conditions, better antiwear ability at rotating speeds under 200 rpm, and optimized wear surface morphology, thus indicating better synergy between PTFE and UHMWPE fabric. Abstract :